The Management of Heavy Menstrual Bleeding After Percutaneous Coronary Intervention in a Woman of Reproductive Age - Gu, Zhi-Chun; Shi, Fang-Hong; Zhu, Jie; Wan, Fang; Shen, Long; Li, Hao (Frontiers in Pharmacology, 2019)
Menorrhagia, during menstrual period, is in place with heavy flow and longer lasting days of bleeding, sequentially leading to anemia. We reported a rare case of menorrhagia in a 33 years-old patient after percutaneous coronary intervention (PCI), who presented with acute coronary syndromes (ACS), uremia and systemic lupus erythematosus before PCI. This patient received three times of hemodialysis weekly (Monday, Wednesday and Friday). On the next day after PCI, this patient began to have menstruation. On the fifth day of menstruation, the patient complained of excessive menorrhagia and physical discomfort, with an urgent need for consultation of gynaecologist. After gynecologist consultation, this patient was under oxytocin treatment. However, two days of oxytocin treatment did not significantly improve menorrhagia. Afterword, the menstrual volume of patients was significantly reduced on eighth days of menstruation after once therapy of testosterone propionate and norethindrone. Regarding the reasons of menorrhagia, Heparin in hemodialysis and antiplatelet drugs utilized (aspirin and clopidogrel) after PCI may be contributors to the menorrhagia. In addition, uterine myoma, cervical canal cyst, renal insufficiency and CYP2C19*2 heterozygous are also possible contributors to menorrhagia. There is no such case of whom had menorrhagia in reproductive age with ACS, uremia and systemic lupus erythematosus under hemodialysis and antiplatelet therapy. More clinical safety data on menorrhagia of reproductive age women who are under antithrombotic therapy are required.